Acceleration Strategy of Ship Reparation Project Using the Ranked Positions Weight Method: Comparative Evaluation Between Adding Manpower and Work Time - Tuswan, Tuswan; Dhuryati, Siti Duwi; Mulyatno, Imam Pujo; Ismail, Abdi; Misbahudin, Saefulloh; Hakim, Muhammad Luqman (Transactions on Maritime Science, 2023)
Delays in settlement of a ship repair project in an Indonesian shipyard are still common, resulting in a schedule that cannot be carried out according to the contract schedule. This study investigates the acceleration duration by calculating the track balance using the Ranked Positions Weight Method (RPWM), used within the scheduling system to obtain a balanced schedule arrangement with an even distribution of labor resources or manpower. This method is used to solve the MT Poka Jo (IMO: 9918119) ship repair's acceleration of duration analysis at the Tegal shipyard in Indonesia. The study aims to achieve efficient project scheduling by reducing project completion time and cost-effectiveness. The analysis was performed to assess the amount of labor produced, network diagram, critical track, balance of the critical track, acceleration of the project's duration, increase in labor, and additional working hours (overtime). The network diagram, which comprises 18 tasks on the important track, has a tracking efficiency of 98% after one day, according to the findings. The addition of labor of 10% could reduce the duration of the project up to 16.92% from 65 days to 54 days, with an increase of cost of 3.83% from the initial condition total cost (from US$ 706.62 to US$ 733.7). On the other hand, with the addition of 3 working hours, a duration acceleration of 10.77% from 65 days to 58 days, with an increasing cost of 59.35% (from US$ 706.62 to US$ 1,126.02) can be obtained. As a result, the increase in labor could be a valuable reference for shipyard personnel to anticipate project completion delays.